Incorporating compound flood events in the weather service value chain - Jian Su; Jonas Wied Pedersen; Ida Margrethe Ringgaard; Morten Andreas Dahl Larsen (npj Natural Hazards)
Abstract Research into compound events is increasing, yet operational implementation remains in its early stages for most meteorological services. Forecasting and warning for compound events require advanced modelling, high-quality data, and local meteorological-geographical knowledge. This study analyses ten years of meteorological warnings from the Danish Meteorological Institute (DMI), focusing on five case studies exemplifying the complexities of compound flood events. We assess event-type categories and their physical and social impacts, highlighting challenges in integrating compound events into national warning systems. A key issue is framing warnings within a defined ‘event’ scale due to real-time hazard overlaps. Our findings stress the need for multi-warning approaches based on forecasted time overlaps to enhance risk communication. Implementing an “informational text advisory” could improve response strategies. These insights not only refine Denmark’s warning services but also provide a framework adaptable to other countries facing compound climate hazards.